Antidiabetic Activity of Endophytic Fungi Extract from Leaves of Kembang bulan (Tithonia diversifolia (Hemsley) A. Gray) Through α-Amylase Enzyme Inhibition - Putri, Hanindita Alifia; Elisa Nurnawati; Widjajanti, Hary (Science and Technology Indonesia, 2025)
Diabetes mellitus is a serious health problem with an increasing number of sufferers. In this context, an important method for controlling blood sugar levels is the derivation of α-amylase enzyme inhibitors from natural materials such as endophytic fungi. Therefore, this research aimed to analyze the potential of endophytic fungi from Tithonia diversifolia leaves as α-amylase enzyme inhibitors, secondary metabolites, as well as the character and identity of potential endophytic fungi. The stages included isolation and identification of endophytic fungi, extraction of secondary metabolites, α-amylase inhibition tests, analysis of bioactive compounds using Thin Layer Chromatography (TLC), and identification of potential endophytic fungi. The results showed that DT3J1 (67.83 µg/mL), DM3J1 (69.36 µg/mL), DT2J2 (80.42 µg/mL), and DT4J1 (88.64 µg/mL) of the eight endophytic fungi isolates reported high potential as inhibitors of the α-amylase enzyme, with IC50 values ​classified as strong. Potential fungal extracts contain bioactive compounds such as alkaloids, flavonoids, phenols, and terpenoids. Meanwhile, molecular identification showed that potential endophytic fungi consisted of Curvularia pseudointermedia, Diaporthe passifloricola, Nodulisporium verrucosum, and Muyocopron laterale species. This research also provided scientific evidence on the potential of the endophytic fungus Tithonia diversifolia as a candidate for antidiabetic drugs.